A systematic review of post-operative infections in pediatric ventriculoperitoneal shunt cases - Farhad Bal'afif; Tommy Alfandy Nazwar; Donny Wisnu Wardhana; Prisca Anindhita; Abdo Rouf El Shadawi; Hatim Sultan; Mochamad Bashir; Mustofa Mustofa (Amaltea Medical Publishing House, 2024)
Background. Hydrocephalus is a prevalent condition in children, affecting both developed and developing countries. Neurosurgical interventions such as ventriculoperitoneal shunts are common, but are associated with a high risk of complications, including infections, which can lead to additional issues and costs. This study aims to review the incidence of infection in pediatric patients before and after ventriculoperitoneal shunt placement, in order to address this issue. Methods. A standard process of analyzing scientific questions using the Population, Intervention, Control, and Outcome (PICO) method was used to develop a protocol for searching research articles in online databases such as PubMed, Cochrane, POPLINE, and Sciencedirect. The articles selected for inclusion in this study met the following criteria: 1) described interventional ventriculoperitoneal shunt placement in pediatrics, 2) focused on cases of ventriculoperitoneal shunt complications with a focus on infection, 3) were published within the last 10 years, and 4) were published in English-language journals with peer review standards. Results. Sixteen articles were identified for review. Seven of these articles mentioned surgical or mechanical interventions as a means of preventing infections, while six articles discussed medical treatment for infection prevention. Three articles described the microorganisms found in cerebrospinal fluid. Conclusion. Future studies should focus on the issues related to ventriculoperitoneal shunt complications and interventions related to immunological, neuroendocrine, and biophysical factors to prevent infections, as well as surgical management and medication administration.